(untitled) (Journal of the College of Basic Education, 2022)
The aim of the study was to identify the effect of exercises with various training methods on some functional and skill capabilities of young players in soccer halls, and the researchers used the experimental approach to suit the nature of the research problem, and the research sample consisted of 40 players from the Rusafa educations (1, 2, 3) They were divided into four groups, the first experimental group, the circular training, the second experimental group, station training, the third experimental group, contrast training and the control group, each group (10) players. The program implementation period lasted (8) weeks and by (3) training units per week (Saturday, Monday, Wednesday). After implementing the training program and conducting the post-test, the researchers reached the most important conclusions, including the superiority of the varying training group in the skill capabilities under discussion and then followed by the circular training group and stations, the circular training group achieved superiority over the rest of the groups in the blood pressure (systolic, diastolic) and heart rate tests, then followed by the mixed training group N then train stations and the control group. The researchers also recommends the necessity of diversification in the use of training methods because of the importance of raising the skills and functional variables, and the need to use the differentiated training method because of its importance in raising the level of skill and physical capabilities and functional changes. Various training methods. Functional capabilities. Exercises